Applying Formative Assessment through Edmodo to Evaluate Students’ Activities in Internship Program - Vega Hesmatantya (Department of Indonesian Language Education, Graduate School, University of Muhammadiyah Prof. DR. HAMKA, 2019)
Along with the curriculum alteration in higher education which the former one changed into KKNI (Kerangka Kualifikasi Nasional Indonesia) based curriculum, several changes occurred in English Education curriculum for bachelor degree. Significant adjustment appears when Pre-service Teaching Program (PPL) is replaced by internship program (Magang). The internship program has not been done in once; otherwise, it is applied three times during the study period. They are Magang 1 (dasar) ,2 (madya) and 3.(karya). This reflective study attempts to find out how Edmodo is used as a collaborative tool for formative assessment in evaluate students’ activity in magang madya or Intermediate internship program and how the formative assessment using Edmodo gives benefit towards students’ internship activity . Thirty six English Education students joined this intermediate internship program and they were divided into four groups to complete their internship in four Muhammadiyah schools in Surabaya. In order to know the benefit of using Edmodo in this evaluation, the participants were asked to fill in the survey. The finding shows that the implementation of formative assessment by using Edmodo as a platform is helpful. The students can do some improvement during their internship activity by considering the feedback given by the supervisor. They also get opportunity to obtain written feedback without having to wait offline meeting with the supervisor in the class. However, the use of Edmodo as a platform is still limited where some students still consider that weekly oral feedback is still needed to complete the written ones.